A perfluorocyclopentene based diarylethene bearing two terpyridine moieties – synthesis, photochemical properties and influence of transition metal ions - Wehmeier, Falk (Beilstein-Institut, 2010)
The synthesis of a perfluorocyclopentene based diarylethene bearing two terpyridine units is reported. Furthermore studies of the free ligand’s photochromism and investigations regarding the influence of various transition metal ions on the photochromic reaction are presented. The photochromism of the central diarylethene unit is strongly dependent on the transition metal present, vice versa the photochromic reaction seems to influence the MLCT transition of a binuclear Ru(II) complex.